Health related quality of life in adults with repaired tetralogy of Fallot: psychosocial and cognitive outcomes. Issue 2 (18th January 2005) - Daliento, L; Mapelli, D; Russo, G; Scarso, P; Limongi, F; Iannizzi, P; Melendugno, A; Mazzotti, E; Volpe, B
Abstract : Objective: To assess the health related quality of life of patients who were operated on during childhood for total correction of tetralogy of Fallot, focusing on the psychosocial and cognitive outcomes. Patients: 54 patients (24 men and 30 women, mean (SD) age 32 (4) years), operated on for total correction of tetralogy of Fallot at mean age of 8.2 years, underwent a cardiological examination, psychological assessment (semistructured interview, Minnesota multiphasic personality inventory), evaluation of quality of life (36 item short form health survey), and neuropsychological assessment with an extensive neuropsychological battery of tests. Results: Psychological characteristics—(1) a lower than normal academic level, (2) a job inadequate for educational level, (3) a preference for an overprotective familiar setting, and (4) a difficulty communicating own corporal image. Denial of the cardiopathy was found to be a common behaviour to normalise functioning. Very few patients had a deficit in memory, learning, or attention functions; rather, patients had a deficit in the executive functions, problem solving, and planning strategies. Conclusions: Despite a satisfactory health related quality of life, there are residual psychological and social problems in addition to impaired cognitive outcomes in the presence of a normal intelligence quotient.